Lee-Carter and the macroeconomy - Katja Hanewald (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2009)
Using data for six OECD countries, this paper studies the effect of macroeconomic conditions on the mortality index kt in the well-known Lee-Carter model. Significant correlations are found with real GDP growth rates in Australia, Canada, and the United States, and with unemployment rate changes in Japan, for the period 19502005. In recent years, the relationship between the state of the economy and mortality is found to change from procyclical to countercyclical in all six countries. Based on these findings, variants of the Lee-Carter model are proposed that capture a substantial fraction of the variation in the mortality index.
Keywords: C32; E32; I12; J11; 330; Demography; Lee-Carter; business cycle; time series model; Sterblichkeit; Makroökonomischer Einfluss; Konjunktur; Schätzung; Australien; Kanada; USA; Japan; Frankreich; Spanien